Design approach for the integration of services in buildings - Fouchal, F; Hassan, TM; Loveday, L (Building services engineering research & technology, 2013)
This paper describes a novel methodology to group building services into a single trunking system at minimal proximal distances between them. The study focused on solving the geometrical complexity encountered in conventional arrangements of building services, while taking into account thermo-physical and electromagnetic interactions between services together with building regulations. The potential solution for delivery and distribution of building services in any number of directions is an ‘onion layers’ type of design, using novel mathematical manipulations based on manifolds of spherical and cylindrical geometries joined using Bezier surfaces. Computer-aided design iterations were undertaken for channelling six building services into a single unit including water, air, electricity and data. It consists of concentric cylindrical-spherical shells superimposed at few millimetres gaps (channels) for which physical prototypes were produced. Practical application: Successfully integrating building services such as water, air, electricity and data into a single trunking delivery system would offer an important advancement in reducing services installation cost, maintenance and the running cost of a building. Current design tools and techniques do not offer any solution for such integration; hence the current development of a multi-services trunking system. Subject to satisfactory compliance with health and safety requirements, plus maintenance issues, the system is proposed for embedding into building construction walls, panels or for placement into a confined space as a first step towards next generation building service. It is foreseen that many industries and business will be involved in the early stage of this development.